The importance of cultural understanding and practical solutions during the handover of a psychotherapy and psychotraumatology program in Northern Iraq into local hands - Kornwachs, Gabriel; Hautzinger, Martin; Kizilhan, Jan (Frontiers in Psychiatry, 2024)
In post war regions, especially in low-income countries, the health care systems often require immediate support. For example, after the terror of the so-called Islamic State of Iraq and Syria (ISIS) in 2014, many internally displaced persons took refuge in the Kurdistan Region of Iraq (KRI). Those displaced by war have had to face the reality that psychotherapy did not exist as a service in the Kurdish health system. Many projects and Non-Government-Organizations (NGOs) that work in post-conflict regions focus on short term and quick response and/or basic psychological services. The implementation of the "Institute for Psychotherapy and Psychotraumatology" (IPP) at the University of Dohuk, follows a long-term approach. The 3-year-program teaches students to become professional psychotherapists, with respect to evidence-based and culturally adapted methods of psychotherapy. To achieve sustainability, the project is working towards handing over the teaching and organizational responsibilities into local hands. This article highlights the chances and challenges during this transition, as well as the importance of cultural understanding and realistic, practical solutions. An honest reflection on existing cultural challenges, e.g. inflexible hierarchical structures or an "old-fashioned" religious view of homosexuality, can then lead to practical solutions. These include winning over local authorities by including them in the process, culturally adapting to customs with the help of educated locals, demonstrating non-authoritarian forms of leadership, and explicitly promoting newly graduated young lecturers into positions of authority.